Hepatorenal Syndrome in the Emergency Department: A Case Report - Win Jim Tan; Mohan Tiruchittampalam (University Library System, University of Pittsburgh, 2015)
Background: Hepatorenal syndrome is a condition where there is functional renal failure in a background of liver disease. It is relatively common in patients with liver cirrhosis and is associated with a high mortality rate if untreated. Results: This is a case report of an 88-year-old Chinese man presenting from a community hospital with a new onset of abdominal distension on a background of cryptogenic liver cirrhosis diagnosed on computed tomography scan. Clinical history and physical findings were consistent with that of fluid overload. Investigations performed indicated acute kidney injury together with liver failure secondary to liver cirrhosis. The patient was diagnosed with hepatorenal syndrome in accordance with the criteria established by the International Ascites Club and managed with an infusion of vasopressin and albumin in the emergency department. He was subsequently admitted to the general ward (gastrology), where he was managed for hepatorenal syndrome, improved clinically and was discharged to the nursing home. Conclusion: Hepatorenal syndrome can be managed effectively with albumin and vasopressin, and such treatment can be started as early as in the emergency department. Acute care physicians should not be hesitant in diagnosing and treating hepatorenal syndrome as early as in the emergency department for appropriate patients.